Studi Literatur Skema Pembiayaan Lembaga Keuangan Mikro Syariah - Irvan Murizal; Andri Soemitra (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
Financing schemes carried out by Islamic microfinance institutions continue to face challenges with the development of these institutions. A unique financing scheme with a prohibition on interest-based financing. The literature study used in this study used data in the form of Scopus indexed articles. Data containing content related to financing schemes for Islamic financial institutions was selected with a total of 18 articles. Furthermore, the stages of research are carried out as described in the research methodology. The findings of this study describe two main financing schemes carried out by Islamic financial institutions, namely: The first scheme is Profit and Loss Sharing (PLS) with mudharabah, musyarakah, muzara'ah and muzaqat contracts. The second scheme is non-PLS, which includes murabahah, bai' salam, ijarah and qard al-hasanah. Other findings in this study describe Islamic MFI financing schemes in several countries such as: in Indonesia there are two financing principles in Islamic MFIs, namely equity financing using PLS mechanisms such as: mudharabah and musyarakah. The second principle is debt-based financing using a non-PLS mechanism. While in Bangladesh the Grameen Bank model was developed, but it is considered not to meet Islamic sharia because it still uses interest. Furthermore Kalanjiam financing scheme in India which is quite successful. Finally, in Latin America and Africa, the village bank model has been successfully implemented in accordance with sharia in Jabal al Hoss, Syria. Keywords: LKMS, Financing, Literature Study